MANAGEMENT OF FOETAL BONE REMNANTS OF A RETAINED MACERATED FOETUS BY PARALUMBAR LAPAROHYSTEROTOMY IN A KANKREJ COW - A. Methai; S. Rangasamy; S. Alagar; R. Arun; K. Nagarajan (Indian Journal of Veterinary and Animal Sciences Research, 2025)
A Kankrej cow was presented to the Large Animal Obstetrical Unit of the Veterinary Clinical Complex, Veterinary College and Research Institute, Theni, with a history of foul-smelling vaginal discharge persisting for past one month and the cow had been previously treated for fetal maceration six months earlier during gestation. Per-vaginal examination revealed that the external os of the cervix was dilated to one finger width, with mucoid, foul-smelling discharge and per rectal examination revealed a hard mass in left uterine horn. Ultrasound examination confirmed the presence of hyperechoic mass in the left uterine horn. Based on the case history, rectal examination and ultrasound findings, the case was diagnosed as foetal bone remnants due to incomplete evacuation of macerated foetus. Despite administering prostaglandin (500 µg IM) to induce cervical dilation, the cervix did not sufficiently dilate. Therefore, laparo-hysterotomy was planned to remove the foetal bone remnants under local and paravertebral nerve block using 2 per cent lignocaine hydrochloride. Post-operative care included antibiotics, anti-inflammatory, antihistamine and supportive therapy for five days along with wound management. The cow had an uneventful recovery, with complete wound healing. Skin sutures were removed 14 days post-operation. The cow exhibited normal estrous cycle after a month of surgery.